مصطفیٰ زیدی کی مستعملہ بحور کا تجزیاتی مطالعہ - Kalsum, Rozina (Tabeer e Nau, 2025)
This article is an effort to comprehend the Prosodic system used by the renowned poet: Mustafa Zaidi. He used meters with excellence and his poetry contained extraordinary poetic qualities which made him distinguished in the recent history of Urdu literature. He used Urdu meters with ease and great mastery and utilize most of the meters available in Urdu poetry. This study will help to understand the system of Aruz available in Urdu language and will guide the researchers on this subject